Cost reduction for the lipid production from distillery and domestic mixed wastewater by Rhodosporidium toruloides via the reutilization of spent seed culture medium. (1st October 2017) - Ling, Jiayin; Tian, Yuan; de Toledo, Renata Alves; Shim, Hojae
Abstract: Previous studies showed that lipids could be produced from non-sterile distillery wastewater using high initial cell density of oleaginous yeast Rhodosporidium toruloides while lots of spent seed culture medium was generated during the seed culture preparation. This study explores the possibility to reuse the spent seed culture medium while saving resource and cost. The cells produced from the 2nd time reused medium without extra nutrient addition showed similar performances to the fresh medium in lipid production (biomass 7.42 ± 0.31 g/L, lipid yield 2.74 ± 0.42 g/L, and lipid content 36.90 ± 4.36%) and removal efficiencies for organics and nutrients (chemical oxygen demand, total nitrogen, and total phosphorus removal of 86.47 ± 1.40%, 50.73 ± 6.15%, and 74.36 ± 3.39%, respectively), in non-sterile distillery and domestic mixed wastewater after two-day cultivation. The 3rd time reused medium showed relatively low removal efficiencies for organics and nutrients as well as poor lipid production at the early culture stage, resulting in the reutilization of 3rd time spent medium not recommended even with 50% nutrient supplementation. Around 30% reduction in the material cost for the medium preparation could be achieved by the spent medium reutilization. Highlights: Reutilization of spent seed culture medium while saving resource and cost. Significant biomass production by 2nd time reused medium. Reused medium with similar lipid productivity to fresh medium. High removal efficiencies for organics and nutrients in real mixed wastewater. Cost reduction of ∼30% for seed culture material by spent medium reutilization.